2019
DOI: 10.1101/508366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Adhesion and Substrate Elasticity on Neutrophil Extracellular Trap Formation

Abstract: Neutrophils are the most abundant type of white blood cells. As part of their immune defense mechanisms they are able to decondense and release their chromatin as neutrophil extracellular traps (NETs). This process (NETosis) also plays an important role in many chronic and inflammatory diseases such as atherosclerosis, rheumatoid arthritis, diabetes and cancer. For this reason, much effort has been invested into understanding biochemical signaling pathways in NETosis. However, the impact of the mechanical micr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…Moreover, several studies have shown that α M β 2 blockade reduced NET release ( 39 , 40 , 69 , 70 ), which indirectly supports our work. Our findings that α M β 2 interaction with ligand may regulate NET formation builds on earlier findings, which showed that PMA stimulation led to high levels (>80%) of chromatin decondensation (a prelude to NET formation) and was not affected by substrate ( 41 ). In contrast, LPS stimulation led to lower basal levels of decondensation (~20%) and levels increased with matrix stiffening and increased cell spreading on β 2 and β 1 integrin ligands.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, several studies have shown that α M β 2 blockade reduced NET release ( 39 , 40 , 69 , 70 ), which indirectly supports our work. Our findings that α M β 2 interaction with ligand may regulate NET formation builds on earlier findings, which showed that PMA stimulation led to high levels (>80%) of chromatin decondensation (a prelude to NET formation) and was not affected by substrate ( 41 ). In contrast, LPS stimulation led to lower basal levels of decondensation (~20%) and levels increased with matrix stiffening and increased cell spreading on β 2 and β 1 integrin ligands.…”
Section: Discussionsupporting
confidence: 89%
“…Having found an effect on NET release, we next examined integrin activation and neutrophil adhesion, which are also implicated in NET induction ( 39 41 ). We measured neutrophil adhesion to primary human endothelial cells in the absence or presence of PMA (a general integrin activator) or LPS (to mimic infectious stimuli), stimuli that induce NETs via distinct pathways ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This manuscript has been released as Pre-Print at BioRxiv (56). We thank Andreas Janshoff and Claudia Steinem for fruitful discussions and support.…”
mentioning
confidence: 99%
“… Liu’s flow cytometry analysis requires cells in suspension, while ours and other studies report actin disassembly during NETosis of adherent cells ( 1 , 3 , 5 ). Neutrophils in situ adhere via integrins to extracellular matrix, other cells, or clots, and integrin engagement to an immobile ligand contributes to NETosis ( 6 , 7 ). While PMA induces integrin activation, the absence of immobile ligands in suspension would fail to initiate integrin-mediated activation of actin regulatory pathways ( 8 ) during NETosis.…”
mentioning
confidence: 99%